Clinically relevant outcome measures for new pharmacotherapy, allergen avoidance and immunotherapy trials in allergic rhinoconjunctivitis. Issue 3 (June 2015) - Pfaar, Oliver; Klimek, Ludger; Gerth van Wijk, Roy
Abstract : Purpose of review: The purpose of this review is to provide a current overview on both primary and secondary measures of efficacy of therapeutic interventions for clinical trials in allergic rhinoconjunctivitis (ARC) patients. In particular, this review highlights similarities and differences regarding endpoints in trials involving allergen immunotherapy (AIT), pharmacotherapy and allergen avoidance and addresses unmet needs regarding these measures in the future. Recent findings: In 2014, the European Academy of Allergy and Clinical Immunology (EAACI) proposed a standard for the definition of the primary endpoint for AIT trials in ARC and, moreover, emphasized the advantages and disadvantages as well as unmet needs considering outcome measures for this treatment. Recently, as an (indirect) comparison of clinical efficacy of different interventions, the relative clinical impact (RCI) has been used to determine the percentage reduction of symptom scores in active versus placebo treatment. Summary: Several primary and secondary clinical endpoints of therapeutic interventions for clinical trials in ARC patients such as AIT or pharmacotherapy have been proposed by the U.S. Food and Drug Administration (FDA) as well as by the European Medicines Agency (EMA). Moreover, recommendations for the implication of these endpoints in clinical trials have been promoted by academia such as the World Allergy Organization (WAO) or the European Academy of Allergy and Clinical Immunology (EAACI). However, an urgent need for the future will be a thorough international harmonization regarding the definition of clinical endpoints, timing of assessments of clinical efficacy and determination of the clinically meaningful and relevant magnitude of efficacy of therapeutic interventions for clinical trials in ARC patients.